Influence of Process Innovation on the Performance of Coffee Cooperatives in Kenya - Kuguru, Peter Ngibuini; Jaensson, Jan-Erik; Nganga, Kinyanjui (Journal of Strategic Management, 2022)
Purpose: The purpose of this paper was to assess the influence of process innovation on the performance of coffee cooperatives in Kenya. Methodology: A descriptive research design was applied. The target population was 525 coffee cooperative societies in Kenya registered with the Commissioner for Cooperatives and licensed by AFFA (Coffee Directorate) as at 30th of October 2016. The sample size was 227 respondents which was arrive at using stratified random sampling technique. Structured questionnaires were used to collect primary data. Descriptive statistic such as means scores and standard deviation and inferential statistics such regressions were used. Findings: The study found that there was a positive relationship between process innovation and the performance of the coffee cooperatives (Î²=0.591, p=0.027). This implied that an improvement in the aspects related to process through which the firm operates relatively multiplies the performance outcomes of cooperatives in a positive manner. Investing in process innovation was found to have the largest and most significant effect compared to investing in organization, marketing and product innovations. Recommendation: The study recommends that for prioritization purposes, coffee societies should prioritize investing in process innovations compared to other innovations, especially if there a limited budget. Policy makers should ensure a favorable environment for process innovations.